Immediate prophylactic vs endoscopic or symptomatic‐driven azathioprine treatment to prevent surgical recurrence after intestinal resection for Crohn's disease. (20th August 2018) - Guo, Z.; Cai, X.; Liu, R.; Gong, J.; Li, Y.; Cao, L.; Wang, Z.; Zhu, W.
Abstract: Aim: Azathioprine can prevent postoperative recurrences in Crohn's disease. We compared the efficacy of azathioprine in preventing surgical recurrence to explore whether immediate prophylaxis after surgery is better than azathioprine started after endoscopic or clinical recurrence. Method: Data of patients with intestinal resection and ileocolic anastomosis for Crohn's disease between 2006 and 2015 were retrieved from a prospectively maintained database. Patients were grouped according to the strategies of postoperative therapy with azathioprine. Univariate and multivariate proportional hazard Cox regression analyses were conducted to identify independent predictive factors for surgical recurrence. Results: Only age equal to or less than 16 years at diagnosis was an independent risk factor for surgical recurrence in all 166 patients ( P = 0.005). In patients with high risk of recurrence (27 in the symptom‐driven group, 39 in the endoscopy‐driven group and 69 in the immediate prophylaxis group), both immediate and endoscopy‐driven azathioprine delayed and reduced surgical recurrence compared with symptom‐driven azathioprine ( P = 0.035, 0.019). Their efficacy in reducing surgical recurrence was confirmed by Cox regression analyses (hazard ratio 0.465, P = 0.045; hazard ratio 0.352, P = 0.028). Surgical recurrence was similar between the immediate and endoscopy‐driven groups. In addition, age ≤ 16 at diagnosis was still an independent risk factor for surgical recurrence in this subgroup. Conclusions: In patients with high risk of recurrence, both immediate prophylactic azathioprine after surgery and azathioprine started after endoscopic recurrence can delay and reduce surgical recurrence compared with azathioprine started after clinical recurrence. In addition, azathioprine started immediately after surgery was not superior to azathioprine started after discovery of endoscopic recurrence.